Guerra, Estado y derecho en Huanta (Ayacucho, Perú) en la Independencia y formación del Estado peruano, 1814-1850 - Pereyra Chávez, Nelson Ernesto (2023)
This article begins with a study of two judicial disputes related to land ownership, which were led by peasants from the Huanta highlands, in the Ayacucho region in Peru. Based on the hermeneutic analysis of the judicial records of the disputes, it argues that these peasants intervened in the lawsuits stimulated by their experience from the independence war and the caudillista conflicts of the 19th century, developing a moral argument that served as a combat weapon to thwart the opponent in the courts and achieve the claim. In this way, they participated in the process of the formation of the republican State, prolonging the violence of war to earlyrepublican law and justice.